Saphenous venous cavernous angioma masquerading as an aneurysm - Luai Zarour; Aaron J. Cunningham; Mubeen A. Jafri (Elsevier, 2019)
Cavernous angiomas are common in the upper body and viscera but saphenous vein cavernous angiomas have not been previously described in the literature. We present a case of a rare congenital vascular malformation of the lower extremity masquerading as an aneurysm in a 4-year-old girl who presented with an asymptomatic right lower leg mass. Ultrasound was concerning for saphenous venous aneurysm and MRI was confirmatory. Operative exploration identified a vascular mass without evidence of an aneurysm; cavernous angioma was confirmed on pathologic examination. Although infantile vascular lesions are common, imaging diagnosis of venous aneurysm - an unusual asymptomatic clinical entity - should raise concerns about possible rare entities or diagnostic alternatives.